Analysis of factors influencing managerial decision to use trade credit in construction sector. Issue 1 (1st January 2018) - Bărbuţă-Mişu, Nicoleta
Abstract: Trade credit is one of the most flexible short-term funding sources for companies and covers a significant part of the financial resources used by firms. Trade credit received makes available financial resources to achieve other economic objectives of the company. The managerial decision to increase or reduce trade credit offered and received or the collection and credit period is influenced by the company's financial performance. The aim of this paper is to analyse the correlation between trade credit receivable/payable and collection/credit period and six measures of financial performance and find if these variables have any impact on the decision to use trade credit. To achieve this aim, we used a sample of 958 European firms from the construction sector which were analysed using correlation and OLS regression, separately on developed and emerging countries. The main results found are: trade credit offered/received is directly correlated with return on equity and firm size, and inversely correlated with return on assets; trade credit offered is directly correlated with current liquidity and long-term banking loans; trade credit received is directly correlated with liquidity ratio and inversely correlated with current liquidity and long-term banking loans; and trade credit offered is inversely correlated with liquidity ratio.